Formation of void in BFS/CACO3 diffusion couple - Ismail, Ahmad Abdul Mun'im; Rozhan, Alya Naili; Rosdin, Muhammad Rafiq Haikal; Purwanto, Hadi; Abdul Hamid, Abd. Malek; Ani, Mohd Hanafi (IIUM Press, 2025)
This study investigates void formation in the blast furnace slag (BFS) and calcium carbonate (CaCO3) diffusion couple, which is critical for understanding the interdiffusion process in cement production. The experimental analysis involved hightemperature diffusion experiments, focusing on the volume fraction of void at the BFS/CaCO3 interface, the activation energy of void formation, and the I-V measurement of void formation at the BFS/CaCO3 interface. Void measurements revealed a 25% increase after exposure to the specified temperature, while the activation energy for void formation was calculated to be – 41.48 kJ/mol. I-V measurements revealed ionic diffusion as the dominant mechanism for void formation, with an average decomposition rate of 1.4598  10-12 m2 s -1 . These findings provide valuable insights for utilizing BFS in cement production.